Folic Acid-Conjugated Nanoniosomes: An Effective Carrier for Targeted Bleomycin Delivery in Oral Cancer - Salehan, Fatemeh; Mohammadi, Yasamin; Shieh, Mobina; Askarizadeh, Mandana; Rahmani, Shokoufeh; Alishahi, Farhad; Hheidari, Ali (Asian Pacific Journal of Cancer Biology, 2025)
Overview: Oral cancer poses significant health challenges with high mortality and systemic side effects from conventional chemotherapy. This study developed folic acid-conjugated nanoniosomes for targeted delivery of bleomycin, leveraging folate receptor overexpression on oral cancer cells to enhance drug delivery and reduce off-target effects. Methods: Nanoniosomes were synthesized via the thin-film hydration method using cholesterol, nonionic surfactants, and folic acid. Bleomycin was loaded into the hydrated lipid film, and the suspension was sonicated to achieve uniformity. Dynamic light scattering (DLS) characterized particle size, PDI, and zeta potential, while scanning electron microscopy (SEM) assessed morphology. Cytotoxicity was evaluated using the MTT assay on folate receptor-positive oral cancer cells treated with varying bleomycin concentrations over 24, 48, and 72 hours. Results: The nanoniosomes averaged 230 ± 15 nm in size with a PDI of 0.21 ± 0.03 and a zeta potential of -28 ± 2 mV, indicating stability. SEM revealed spherical, smooth particles. Cytotoxicity tests showed a time- and dose-dependent reduction in cell viability, with IC50 values decreasing from 20 µM at 24 hours to 10 µM at 72 hours. Conclusion: Folic acid-conjugated nanoniosomes demonstrated effective targeted delivery of bleomycin, enhancing cytotoxicity and minimizing systemic toxicity. These findings support further investigation for clinical applications in oral cancer therapy.